2018
DOI: 10.1109/tnsre.2017.2768500
|View full text |Cite
|
Sign up to set email alerts
|

C–FSCV: Compressive Fast-Scan Cyclic Voltammetry for Brain Dopamine Recording

Abstract: This paper presents a novel compressive sensing framework for recording brain dopamine levels with fast-scan cyclic voltammetry (FSCV) at a carbon-fiber microelectrode. Termed compressive FSCV (C-FSCV), this approach compressively samples the measured total current in each FSCV scan and performs basic FSCV processing steps, e.g., background current averaging and subtraction, directly with compressed measurements. The resulting background-subtracted faradaic currents, which are shown to have a block-sparse repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It has been used, among other techniques, to detect dopamine, noradrenaline, serotonin, and indoleamine with carbon fiber electrodes because neurotransmitters oxidize at a low voltage [8,9]. It has been reported that FSCV was used in vitro, in vivo, on neuron cells and brain slices, and on anaesthetized or freely moving animals [10][11][12]. The voltammograms (current vs. voltage) obtained by these techniques are in theory specific to a given substance and may be used to determine precisely each neurotransmitter, as explained by Hermans et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used, among other techniques, to detect dopamine, noradrenaline, serotonin, and indoleamine with carbon fiber electrodes because neurotransmitters oxidize at a low voltage [8,9]. It has been reported that FSCV was used in vitro, in vivo, on neuron cells and brain slices, and on anaesthetized or freely moving animals [10][11][12]. The voltammograms (current vs. voltage) obtained by these techniques are in theory specific to a given substance and may be used to determine precisely each neurotransmitter, as explained by Hermans et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various implementations of thresholding for spike detection have been reported (102,103). Compression techniques have also been demonstrated on neural spikes using optimized vector quantization methods (104), CS (105)(106)(107), wavelet transform (108,109), Walsh-Hadamard transform (98), and spiking band power calculation (99,110). Wavelet transform-and Walsh-Hadamard transform-based techniques retain information on both the occurrence and the shape of the spike.…”
Section: Spike Detection For Neural Sensingmentioning
confidence: 99%